The role of Fas ligand protein in the oxidative stress induced by azoxymethane on crypt colon of rats - Bussuan,Luiz Antonio Maksoud (2010)
PURPOSE: To study the protein Fas ligand (FasL) on the expression of apoptosis, using a model of oxidative stress induced by azoxymethane (AOM), in the crypt of colon in rats. METHODS: Wistar rats (n=14) were assigned into two groups: control (n=7) and AOM (n=7). A single subcutaneous administration of AOM (5mg/kg) or saline solution was performed at the beginning of third week and after three hours samples of proximal colon were collected. The expression of FasL was quantified (Software ImageLab) in percentage of areas in the top, base and all crypt. Results were expressed as mean ± sd (Shapiro-Wilks test and t Student test) (p < 0.05). RESULTS: In the animals of CG there was no significant difference between the FasL expression of the top (10.75±3.33) and basal (11.14±3.53) colon crypt (p=0.34293740). In the animals of AOM there was no significant difference between the FasL expression of the top (8.86±4.19) and basal (8.99±4.08) colon crypt (p=0.78486003). In the animals of CG (10.95±3.43) and AOM (8.92±4.13) there was a significant difference of the FasL expression (p=0.026466821). A significantly decrease on the FasL expression was observed in the animals of CG (10.75±3.33) and AOM (8.86±4.19) in the top crypt (p=0.00003755*). A significant decrease was also observed in the animals of CG (11.14±3.53) and AOM (8.99±4.08) in the basal colon crypt (p=0.00000381**). CONCLUSION: Azoxymethane induce the oxidative stress and the significantly decrease of FasL expression, although there is no significant difference between basal and top of colon crypt linked to consumption-activation of Fas ligand.